Bicruciate-retaining total knee arthroplasty, a promising technology, that’s not quite there - Barrett, Thomas J.; Shi, Lei; Parsley, Brian S. (Annals of Translational Medicine; Vol 5, Supplement 1 (May 15, 2017): Annals of Translational Medicine, 2017)
In the April 2016 study published by Christensen et al. retrospectively compared patients undergoing total knee arthroplasty (TKA) with a newer bi-cruciate retaining (BCR) design versus standard PCL retaining (CR) TKA. The group appropriately identifies that historically up to 25% of patients undergoing TKA are dissatisfied with the result (1,2). Because of this alarming level of dissatisfaction following TKA, newer designs have aimed at retaining the anterior cruciate ligament (ACL) with hopes of restoring more native kinematics in the reconstructed knee. Studies have shown that these newer BCR designs indeed provide more natural knee kinematics (3,4).